Legal protection of consumers against e-commerce digital transactions review of state authority in guaranteeing citizens' constitutional rights - Anderson, Kevin; Cornelis, Vieta Imelda; Marwiyah, Siti; Astutik, Sri (Law and Economics, 2025)
The rapid development of information and communication technology has transformed the trade sector through the emergence of digital transactions. In this context, there has been a shift in the relationship between businesses and consumers, giving rise to new challenges in consumer rights protection. The complexity and intensity of digital transactions open up opportunities for exploitative practices that harm consumers as the more vulnerable party. The main issue examined in this paper is how the state, from a constitutional law perspective, exercises its authority to ensure legal protection for consumers in digital transactions as part of fulfilling the constitutional rights of citizens. This study employs a normative legal method with a qualitative analytical approach, through literature review and grammatical and systematic legal interpretation. The results indicate that consumer protection in digital transactions is an integral part of the principles of the rule of law and human rights protection as stipulated in Article 28D paragraph (1) of the 1945 Constitution. The state is obligated to actively implement adaptive regulations, strong oversight, and consumer education to create a fair, safe, and sustainable digital trade ecosystem in accordance with the values of social justice and humanity as enshrined in Pancasila.